The Metabolites of Lactobacillus fermentum F-B9-1 Relieved Dextran Sulfate Sodium-Induced Experimental Ulcerative Colitis in Mice - Su, Le; Ma, Feifan; An, Zaiyong; Ji, Xiuyu; Zhang, Ping; Yue, Qiulin; Zhao, Chen; Sun, Xin; Li, Kunlun; Li, Baojun; Liu, Xinli; Zhao, Lin (Frontiers in Microbiology, 2022)
The incidence of ulcerative colitis (UC) is increasing globally and has become a global health issue. Current therapies for UC are not totally effective, resulting in persistent and recurrent disease for many patients. It has been reported that metabolites of Lactobacillus fermentum contains immunomodulatory molecules and might be a novel therapy for UC. In this manuscript, the metabolites of Lactobacillus fermentum F-B9-1 (MLF) was screened to investigate the ameliorative effects on UC. The MLF below 2 mg/ml did not decrease the cell viability of Caco-2 cells. The ELISA and RT-PCR results showed that MLF significantly decreased the levels of IL-1β and IL-6 in lipopolysaccharide (LPS)-induced Caco-2 cells. The levels of Occludin and ZO-1 were improved after MLF treatment. Then, the MLF was gavaged in the dextran sulfate sodium (DSS)-induced UC model mice. The results showed that MLF ameliorated colitis symptoms in mice. It reduced the loss of body weight and disease activity index (DAI) scores, inhibited the colon length shortening and elevated the histopathological scores. Additionally, MLF suppressed pro-inflammatory cytokine expression and improved tight junction protein expression in DSS-induced UC. Furthermore, the use of MLF remodeled the diversity of the gut microbiota and increased the number of beneficial microorganisms. Finally, the different components of MLF were separated to investigate which constituent played a role in UC. Only exopolysaccharides and protein from MLF could decrease the levels of IL-6 and IL-1β in LPS-induced Caco-2 cells. Overall, the results demonstrated that MLF relieved DSS-induced UC in mice. And MLF might be an effective therapy method to treat UC in the clinic in the future.